Appartenance confessionnelle et allégeances politiques : William Hale White (« Mark Rutherford ») et l’évolution de la non conformité religieuse en Grande-Bretagne au XIXe siècle - Jean-Michel Yvard (Revue LISA)
In his fictional autobiographical writings, William Hale White describes the agonies of religious doubt in the middle of the 19th century. But he also adopts a sociological approach in many of his narratives, in which the fragmentation of the British religious scene is described with great subtlety, and even irony. This article studies this dimension of his writings, proposing a few more contemporary perspectives concerning the differences that have characterized the link between religion and politics in France and in Great Britain.